The Effects and Treatments for Usher Syndrome: A Review - Heerlie, Devita Mayanda; Margaretha, Febrina; Fugaha, Daniel Ryan; Parikesit, Arli Aditya (Indonesian Journal of Life Sciences, 2024)
Usher syndrome is defined as the rare genetic disorder that affects both vision and auditory. Although the prevalence is really low, only about 4 to 17 per 100,000 people, it is noted to cover at least 50% of deaf-blindness cases. After reviewing the molecular genetics from several papers, there are several causative genes found with the most prevalent being MYO7A, and USH2A that cause USH type 1 and 2 respectively. Furthermore, other literature has found promising treatments that may help to slow down or prevent further degeneration of the syndrome.